Traceability in Digital Forensic Investigation Process - Selamat, S. R.; Yusof, R.; Sahib, S.; Abdollah, M. F.; Hassan, N. H.; Zainal Abidin, Z. (2011)
Digital forensic is part of forensic science that implicitly covers crime that is related to computer technology. In a cyber crime, digital evidence investigation requires a special procedures and techniques in order to be used and be accepted in court of law. Generally, the goals of these special processes are to identify the origin of the incident reported as well as maintaining the chain of custody so that the legal process can take its option. Subsequently, the traceability process has become a key or an important element of the digital investigation process, as it is capable to map the events of an incident from difference sources in obtaining evidence of an incident to be used for other auxiliary investigation aspects. Hence, this paper introduces a trace map model to illustrate the relationship in the digital forensic investigation process by adapting and integrating the traceability features. The objective of this integration is to provide the capability of trace and map the evidence to the sources and shows the link between the evidence, the entities and the sources involved in the process, particularly in the collection phase of digital forensic investigation framework. Additionally, the proposed model is expected to help the forensic investigator in obtaining accurate and complete evidence that can be further used in a court of law.